Interrelationship Between Tribal Religion and Economy: Analysis of Kandha Tribe of Odisha - Behera, Simpul (The Eastern Anthropologist, 2024)
As far as Kandha of Kandhamal are concerned, their supreme deity has always been Dharni Penu- the Earth Goddess. Like the ancient Egyptians who used to be known as the children of the Sun God, these indigenous people of Odisha are also identified as the c
Keywords: Economy; Kandha; Ritual; Society; Religion